A new generation, promising engineering material: Cubic boron nitride c-BN - Baris Cetin; Goksel Durkaya; Hakan Kaplan (Hittite Journal of Science and Engineering, 2015)
In order to meet the design requirements and expanding demands in various engineering fields, it is essential to incorporate new technological improvements in material sciences into existing processes and applications. This involves engineering new material systems and improving existing ones towards higher strength, toughness and wear resistance. In this context, cubic boron nitride c-BN , which is a special polymorph of boron nitride, seems to be a high-potential candidate for engineering solutions due to its great mechanical and chemical properties. In this article, advantages and disadvantages of c-BN material system are presented with respect to our ongoing research efforts. The preliminary results about the characterization study of thin film c-BN coatings with Raman spectroscopy are also presented